Elucidating the aluminum storage mechanism in cobalt sulfide cathode materials for advanced batteries - Ruiyuan Zhuang; Ruiyuan Zhuang; Yongqing Li; Junhong Wang; Jianfeng Zhan; Jiangnan Yan; Yaru Chen; Wenhui Mo; Jun Zhang; Jun Zhang (Frontiers in Chemistry, 2025)
Rechargeable aluminum-ion batteries (AIBs), as novel energy storage systems featuring low-cost, high-energy density, and superior safety, demonstrate promising potential as a next-generation battery technology. However, the lack of high-performance cathode materials remains a critical barrier to practical implementation. In this study, highly crystalline cobalt sulfide (Co9S8) nanoparticles were synthesized using a one-step hydrothermal method and systematically evaluated their electrochemical performance and energy storage mechanisms in AIBs. Structural characterization revealed that while the synthesized material maintained high crystallinity, it formed agglomerates during the synthesis process that induced severe electrode polarization and limited ion diffusion kinetics. Electrochemical analysis demonstrated a reversible capacity of 48 mAh g−1 after 500 cycles at a current density of 100 mA g−1, indicating moderate cycling stability. DFT calculations with Bader charge analysis provided atomic-scale insights, revealing that Al3+ preferentially occupies Co. lattice sites through a pseudo-isomorphic substitution mechanism, exhibiting a 52.5% lower formation energy compared to S-site substitution. This work establishes critical correlations between morphological characteristics and electrochemical performance while proposing a novel cation substitution mechanism for energy storage. These findings provide fundamental insights for designing high-kinetics transition metal sulfide cathodes and advance the development of practical multivalent-ion battery systems.